La biofertilizacion en la montaña: herramienta biotecnologica de la agricultura sostenible - Planes Leyva, M.=700 1 Utria Borges, E.; Figueroa Santana, I.; Lamothe, T.; Calderon Aguero, J.; Gonzalez Paneque, O.S.
(Es, En)
Ilus., 6 ref.
Keywords: BIOFERTILIZANTES; AZOTOBACTER; AGRICULTURA SOSTENIBLE; CUBA; FOSFORINA